Climate Change and Human Displacement: Towards Validation of Rights (Revista Justiça do Direito, 2025)
Climate migration presents a series of heterogeneous and awkward problems. There is a sharp disagreement on climate change as a triggering reason for human migration, both internal and cross-border. The trails of these relocations unwrap a vista of provocative accounts.  Yet, the central concern is not how they move to a safer zone or expose themselves to additional risks.  Rather, we encounter the absence of a normative framework to support the claims of the groups of these ill-fated people who get displaced because of disastrous environmental events. The debate here is partly about the scientific uncertainty of acceding to the branding of ‘climate’ migrant status and partly about the lack of international legal denomination to isolate such a group as ‘migrants’ with all its variants. Here, a slice of the global narrative revolves around the repudiation of climate change-induced migration. The 1951 Convention is hardly beneficial for climate migrants, and this deficiency is rooted in the Convention’s inability to incentivize states, giving birth to a thin legal framework. Additionally, the international climate change regime has been unsuccessful in producing any synergy with international refugee law. In this paper, we argue that this lack of interaction originates in the questionable application of state sovereignty doctrine that has blemished international refugee law and climate change negotiation. In the wake of a diminishing window of choice, there is a need to upgrade the climate change negotiation mandate to include a clear state obligation requirement to recognize the rights of climate migrants. This claim is entirely consistent with the dynamic structure of international climate governance and holds the potential to advance a code of ‘collective rationality’ over narrow state interests.